2019
DOI: 10.3390/pharmaceutics11110559
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Encapsulated Liposome Delivery System: An Effective Treatment Approach against Breast Cancer

Abstract: This study aimed at developing metformin hydrochloride (Met) encapsulated liposomal vesicles for enhanced therapeutic outcomes at reduced doses against breast cancer. Liposomal Met was prepared using thin-film hydration through various loading methods; passive loading, active loading, and drug-loaded lipid film. The drug-loaded film method exhibited maximum entrapment efficiency (~65%) as compared to active loading (~25%) and passive loading (~5%) prepared Met-loaded liposomes. The therapeutic efficacy of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…3D spheroid culture methods provide a way to evaluate a drug candidate ex-vivo while mimicking the in-vivo appearance and behavior of tumor mass. We recently described the capability of spheroid cell culture studies to mimic the in-vivo features of tumors [39]. This spheroid study was conducted utilizing two kinds of models, prophylactic and therapeutic, which differ significantly in tumor growth and treatment strategies.…”
Section: D Spheroid Studymentioning
confidence: 99%
“…3D spheroid culture methods provide a way to evaluate a drug candidate ex-vivo while mimicking the in-vivo appearance and behavior of tumor mass. We recently described the capability of spheroid cell culture studies to mimic the in-vivo features of tumors [39]. This spheroid study was conducted utilizing two kinds of models, prophylactic and therapeutic, which differ significantly in tumor growth and treatment strategies.…”
Section: D Spheroid Studymentioning
confidence: 99%
“…In recent years, a variety of MET-encapsulated nanocarriers have been developed for anticancer therapy, including liposomes, nanomicelles, polymeric NPs and inorganic NPs. Among them, MET-encapsulated liposomal vesicles were widely investigated (Lee et al 2020;Magdy et al 2017;Osama et al 2019;Shukla et al 2019). For instance, Shukla et al prepared MET-encapsulated liposomes with enhanced therapeutic efficacy against breast cancer (Shukla et al 2019).…”
Section: Met-encapsulated Nano-dds For Cancer Therapymentioning
confidence: 99%
“…Among them, MET-encapsulated liposomal vesicles were widely investigated (Lee et al 2020;Magdy et al 2017;Osama et al 2019;Shukla et al 2019). For instance, Shukla et al prepared MET-encapsulated liposomes with enhanced therapeutic efficacy against breast cancer (Shukla et al 2019). Thin-film hydration method was utilized to prepare the liposomes (Shukla et al 2019).…”
Section: Met-encapsulated Nano-dds For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to its low price, safety, potential cardiovascular protection, and no incidence of weight gain, metformin has been approved for initial therapy of T2DM [ 4 , 5 ]. Recently, clinical studies have indicated that metformin may improve outcomes of several cancers and reduce cancer risk in diabetic patients [ 6 ]. Some other studies showed that metformin might extend the lifespan of people, which led to the ongoing clinical trial “Targeting Aging with Metformin”, aimed at lateness, the process of aging and extend healthy lifespan [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%